2018
DOI: 10.1111/tpj.13989
|View full text |Cite
|
Sign up to set email alerts
|

Structural and biochemical approaches uncover multiple evolutionary trajectories of plant quinate dehydrogenases

Abstract: Quinate is produced and used by many plants in the biosynthesis of chlorogenic acids (CGAs). Chlorogenic acids are astringent and serve to deter herbivory. They also function as antifungal agents and have potent antioxidant properties. Quinate is produced at a branch point of shikimate biosynthesis by the enzyme quinate dehydrogenase (QDH). However, little information exists on the identity and biochemical properties of plant QDHs. In this study, we utilized structural and bioinformatics approaches to establis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 56 publications
2
16
0
Order By: Relevance
“…It appears plausible that following loss of QDH genes, some descending lineages faced selection pressures to regain QDH activity. This has indeed been found by Gritsunov et al (2018), who identified a recent SDH duplicate within the Brassicaceae that gained QDH independently.…”
Section: Discussionsupporting
confidence: 60%
See 4 more Smart Citations
“…It appears plausible that following loss of QDH genes, some descending lineages faced selection pressures to regain QDH activity. This has indeed been found by Gritsunov et al (2018), who identified a recent SDH duplicate within the Brassicaceae that gained QDH independently.…”
Section: Discussionsupporting
confidence: 60%
“…Gritsunov et al . () identified a co‐factor shift from NADP to NAD within the angiosperm QDH clade and proposed an associated differentiation between catabolic and anabolic QDH functions within the angiosperm QDH clade. Furthermore, minute activity towards gallic acid biosynthesis has been detected in SDH enzymes from grape and walnut (Muir et al ., ; Bontpart et al ., ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations